PROCESS CONSULTATION FOR QUALITY ASSURANCE IN SCHOOLS IN VRANCEA COUNTY - Paul BLENDEA; Irina GEANĂ (National Centre for Policy and Evaluation in Education, 2018)
The training program "Process Consultation - an Intervention Model" is conceptually covered by the existing management and quality assurance system in Romania, starting from the premise that any activity carried out in school should have as aim to improve quality, reflected in pupils through good and very good results, "wellbeing" and the progress they have made. The purpose of this program was to give access to certain information necessary in day to day activity and also to bring consciousness to those involved in managerial tasks in school. 100 school principals from Vrancea County were trainees in the consultation process with a long term aim: improving the quality of learning and teaching in school.